The impact of Turkey's economic crisis of February 2001 on the tourism industry in Northern Cyprus - Okumus, Fevzi; Altinay, Mehmet; Arasli, Huseyin (Elsevier Ltd, 2005)
This study investigates the impact of the February 2001 economic crisis in Turkey on the tourism sector in Northern Cyprus. A case study approach was followed. Empirical data were collected from 78 hotels in Northern Cyprus through the distribution of a questionnaire and by conducting a series of semi-structured interviews. The research findings reveal that the overwhelming majority of firms participating in the study did not foresee the economic crisis in Turkey. They therefore failed to take any advance measures to deal with it. The economic crisis was found to have had both a negative and positive impact on the tourism industry in Northern Cyprus, although the negative impact seems to have been greater. Implications of the findings are discussed and several recommendations for practice and for future research are provided. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Conflict; Crisis; Cyprus; Hotel; Industry; Island; Management; Tourism